Lung dust content in idiopathic pulmonary fibrosis: a study with scanning electron microscopy and energy dispersive x ray analysis. Issue 5 (May 1991) - Monsó, E; Tura, J M; Pujadas, J; Morell, F; Ruiz, J; Morera, J
Abstract : Examination with an optical microscope and polarised light is not sensitive enough to detect low diameter asbestos fibres. This limitation implies that some cases of asbestosis can be erroneously diagnosed as idiopathic pulmonary fibrosis (IPF) if asbestos bodies are not found in the standard examination of abnormal tissue. To determine whether IPF is over-diagnosed, a study was carried out with scanning electron microscopy (SEM) and energy dispersive x ray analysis (EDXA) on 25 samples previously diagnosed as IPF at the standard examination. Scanning electron microscopy will show the presence of low diameter fibres in the lung without tissue destruction, and these fibres can be identified using EDXA. The quantitative and qualitative results for lung tissue from patients diagnosed as having IPF were compared with the results of the examination of 25 samples of normal lung. Most of the samples from patients diagnosed as having IPF showed only occasional inorganic particles (less than 10 particles/SEM field at 160 x), results equivalent to the results obtained in normal lung. Two cases of IPF, however, showed innumerable asbestos fibres (greater than 100 fibres/SEM field). One of these two patients had an antecedent of brief exposure to asbestos. No environmental antecedent was found in the second patient. Asbestosis was the final diagnosis for these two patients. The examination of inorganic particles in normal lungs showed mainly non-fibrous silicates (61.4%) and particles of heavy elements (34.9%). Only one asbestos fibre was found (0.9%). It is concluded that standard pathological techniques overdiagnose IPF in a few cases in which asbestos bodies are not found with the optical microscope.